Islam, law and the state in Southeast Asia volume 1 - Lindsey, Timothy , 1962- (Islam, law and the state in Southeast Asia, 2012)
Southeast Asia has the world's largest Muslim population - Indonesia alone is home to more Muslims than the entire Middle East - yet nowhere in the region has a theocratic government emerged. Instead, Southeast Asian Islam is characterized by heterodox local traditions